Tuberkuloza dojke - redka oblika zunajpljučne tuberkuloze - prikaz primera - Regvat, Jurij (Zdravniški vestnik, 2004)
Background. There is a decline in incidence of tuberculosis in Slovenia. In most patients a tuberculosis occurs in pulmonary form. In one third of patients it appears either as combined pulmonary and extrapulmonary tuberculosis or extrapulmonary form alone, where pleura and lymph nodes are most often affected. Other localizations are rare and therefore sometimes not taken into account. Patient and methods. We present a female patient with tumorous formation in the breast, clinically and radiologicaly suspicious for neoplastic nodule. Citological examinations did not confirm neoplasm. Further microbiological and citological examinations proved the rare form of extrapulmonary tuberculosis. In addition, we also confirmed a pulmonary tuberculosis. At the end of treatment, improvement in radiological picture of the breast, clinical improvement and negativisation of cultures for Mycobacterium tuberculosis were observed. Conclusions. Determination of tumorous formations in the body is crucial because of appropriate treatment and different prognosis. Tuberculosis can grow anywhere in the body.
Keywords: Breast; Dojka; Pljučna tuberkuloza; Tuberculosis; Tuberculosis, pulmonary; Tuberkuloza